Pengaruh Teknik Masase Counterpesure Mengurangi Rasa Nyeri Persalinan Pada Ibu Inpartu Kala I Fase Aktif Di Puskesmas Darul Aman Aceh Timur Tahun 2023 - Ester Simanullang; Nurmadiah Nurmadiah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Delivery assistance is a delivery service process that starts from stage I to stage IV of delivery. The achievementcofcmaternal healthc effortsc isc measured through the indicator of the percentage of deliveries assisted by qualified health workers (Ministry of Health of the Republic of Indonesia 2015).Based on the description above, the problem discussed in this research is: to determine the effect of counterpressure massage techniques to reduce labor pain in active phase first stage mothers at Darul Aman Community Health Center, East Aceh. The type of research used is quasi-experimental with a pre-test design and post test control group design, cause or risk and effect variables or cases that occur in the research object are measured or collected simultaneously (at the same time) (Notoatmodjo, 2012) Darul Aman East Aceh Community Health Center is a BPJS Health First Level Health Facility in Aceh Tkmur Regency whose address is Jalan Medan, Gp Kuede Village, Darul Aman District, East Aceh Regency, NAD. The Darul Aman Health Center in East Aceh has the Motto: SIMPATI, namely Smiling and Greeting, Informative, Serving, Professional, Accountable, Transparent, Sincere. Based on the results of the analysis and discussion of research results, conclusions can be drawn regarding the effect of massage techniques to reduce labor pain at the Darul Aman Community Health Center, East Aceh. 1. The level of labor pain before the counterpesure massage was performed, all respondents experienced severe pain. 2. The level of labor pain after the counterpesure massage was performed. Most of the respondents experienced moderate pain. 3. There was an effect of using massage techniques to reduce labor pain in mothers during the first stage of the active phase.